El color como elemento narrativo en la producción audiovisual - Chiriboga Hinojosa, Gabriel Alejandro (2017)
Color contains meanings that are accepted and valued in a given society. These meanings are linked to the emotions in the subjectivity of the human and his life experience. The audiovisual production takes these chromatic elements to narrate in a systematic way, facts of fiction that from the beginnings of the audiovisual production have captivated the man. This work is an approximation to understand the process of the color in storytelling and how it is used to reinforce ideologies, feelings and exemplify situations. It is complex to talk about audiovisual production in general, so it is going to be treated specifically the cinema in all its extension, since it is one of the most appropriate examples to speak of color and visual narrative, therefore it has taken as reference the cinematographic genre cyberpunk, specifically to The Matrix of 1999, detailing in detail the uses of color and its ideological and psychological intentionality.